Perceived Cognitive Function and Related Factors in Korean Women With Breast Cancer - Seongmi Moon, PhD, RN; Sun-Hee Kim, PhD, RN, ANP; Mi-Ja Kim, RN, CNS (Elsevier, 2011)
The aim of this study was to explore perceived cognitive function and its related factors in breast cancer patients that had received or were receiving adjuvant chemotherapy after surgery. Methods: A cross-sectional and correlational design was used in this study. A total of 118 women who had undergone or were undergoing adjuvant chemotherapy after breast cancer surgery recruited from a convenience sample from a university hospital in Korea were included in the study. The attentional function index was used to measure perceived cognitive function while the linear analogue self-assessment scale was used to measure mood disturbance. Hierarchical multiple regression analyses were done to determine possible predictors of perceived cognitive function in patients with breast cancer. Results: Perceived cognitive function and mood disturbance had a mean score of 66.22 (SD= 13.43) and 159.78 (SD = 81.40), respectively. Mood disturbance was a statistically significant predictor of cognitive function in patients with breast cancer. Conclusions: Breast cancer patients with mood disturbance may experience decrements in perceived cognitive function. Nurses should be aware of mood changes and its influence on perceived cognitive function in breast cancer patients.